Eradication Suggestions For Infectious Diseases Based on the Fractional Guinea-Worm Disease Model - Öztürk, Bahar Acay (My University, 2024)
Guine-worm disease (GWD) is considered one of the most fascinating infectious diseases that almost no one is aware of. On the other hand, unfortunately, there is no medicine or vaccine to treat this tropical disease transmitted through drinking water. However, GWD is about to be miraculously eradicated. This feature makes it the first parasitic disease to be eradicated without biomedical interventions. Accordingly, this situation brings the question: How can a disease be eradicated without medicine, vaccine or immunity? In light of this question, the current study offers recommendations on how to stop the spread of infectious diseases. One of the best ways to eliminate existing diseases is to benefit from the strategies followed for diseases that have been eradicated. Our results obtained by utilizing the fractional Caputo derivative show that behavior change programs aimed at reducing or stopping the spread of infectious diseases are effective tools in eradicating the disease
Keywords: Mathematical biology; Caputo fractional operator; Fractional modeling; Guinea-worm disease; Non-local derivative